Trichomonas Vaginalis infection among women attending in the public service in Rio Grande do Sul, Brazil: frequency, risk factors and clinical signs - Bruni, Mirian Pinheiro; Lopes, Ângela Sena; Stauffert, Dulce; Santos, Carolina Caetano dos; Cunha Filho, Nilton da; Santos, Luciana Siqueira Silveira dos; Santos, Laura Maria Jorge de Faria; Silveira, Mariângela Freitas da; Farias, Nara Amélia da Rosa (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Trichomoniasis is a cosmopolitan disease that can affect the female fertility, and is commonly underdiagnosed, both in private practices and in public health services, because of the low sensitivity of the wet mount exam used routinely. Objective: To understand the occurrence of T. vaginalis infection by means of in vitro culture in women receiving care in a public health unit, in the city of Pelotas, Rio Grande do Sul, Brazil, as well as to identify the possible risk factors associated with this infection. Methods: Cross‑sectional study was carried out, which included 201 women undergoing interview and gynecological exam, with the collection of vaginal discharge in the Gynecology Ambulatory at the School of Medicine of Universidade Federal de Pelotas. The material collected was examined in the form of fresh smears and cultivated in Diamond’s medium. Epidemiological data were obtained by means of patient interviews and clinical trials, from the medical records. The results were statistically analyzed through χ2 and Fisher’s exact tests, using version 9.0 of the Statistix program. Results: The occurrence of T. vaginalis infection was 7% (14/201). In the wet mount exam, used routinely for the diagnosis of this agent, only 42.85% of the infected women (6/14) were positive. It was noted that 21.4% of the infected women were asymptomatic, and 89.05% were not aware of the existence of the Trichomonas vaginalis infection. Factors independently associated with the infection were the smoking habit (odds ratio [OR] = 11.8), not having a stable sexual partner (OR = 6.36), presence of vaginal discharge with odor (OR = 5.65), and altered vaginal microbiota (OR = 5.31). Conclusion: T. vaginalis infection was present among the women studied, being underestimated because of the diagnostic technique, and because many of them were asymptomatic. The smoking habit, not having a stable sexual partner, having fetid discharge, and altered vaginal microbiota are the risk factors for infection